ACL-deficient knee and unicompartmental OA: state of the art. Issue 3 (22nd February 2017) - Adravanti, Paolo; Budhiparama, Nicolaas C; Berend, Keith R; Thienpont, Emmanuel
Abstract : Anteroposterior knee joint laxity because of anterior cruciate ligament (ACL) insufficiency produces various degenerative changes in the joint, including intra-articular damage, meniscal tears and varus morphology leading to gradual thinning of the cartilage and resulting in posteromedial osteoarthritis (OA). Two different scenarios of medial OA and ACL tear need to be identified to ensure correct surgical planning and minimise the risk of poor surgical outcome. OA development of the medial compartment of the knee may be due to ACL failure or the ACL failure can be a consequence of the arthritic phenomenon within the knee. One of the most important causes of failure in unicompartmental knee arthroplasty (UKA) surgery is the absence of ACL and the majority of failures after UKA without ACL reconstruction occur because of tibial loosening, which tends to occur early. Patients eligible for combined UKA and ACL reconstruction are typically young adults with a history of previous trauma and untreated ACL rupture, joint instability, and consequent OA of the posteromedial part of the knee. In order to obtain a correct diagnosis, a detailed medical history, complete physical examination and detailed radiographic protocol are mandatory. ACL reconstruction combined with UKA is a technically demanding procedure and must be performed in well-defined steps. A significantly higher failure rate was noted in patients who did not undergo ACL reconstruction as compared with those who received a combined procedure. Unicompartmental knee arthroplasty combined with ACL reconstruction is an excellent surgical solution for posteromedial osteoarthritis secondary to ACL deficiency.